MOTIVASI ANGGOTA KELOMPOK WANITA TANI PUSPITA PADA KELOMPOK TANI KLANTUM DALAM MEMBUDIDAYAKAN TANAMAN HIAS BUNGA KRISAN DI DESA HARGOBINANGUN KECAMATAN PAKEM KABUPATEN SLEMAN - Dewantoro, Vandrias; Heni, Heni; Maya, Maya (Jurnal Dinamika Sosial Ekonomi, 2010)
Motivation owned by Puspita Woman Farming Group member informing group Klantum in cultivating adorned plant of Chrysanthemum in Hargobinangun village Pakem Sub District, Sleman District. The objective of this research is to know the rate of motivation owned by KWT Puspita’s members in farming group Klantum in cultivating Chrysanthemum and to analyze the influence of talent, knowledge, favorite, admission, environment, friends, facilities, and leisure time towards motivation owned by KWT Puspita ‘s member in farming group Klantum in cultivating adorned plant of Chrysanthemum. This research uses descriptive method. The research method uses study case method. The method of choosing respondentin this research is census method. It used I5 people. The result of the research shows that the rate of motivation owned by KWT Puspita’s members in farming group Klantum in cultivating Chrysanthemum belongs to high rate categorized. The factors giving positive influence motivation by KWT Puspita’s members in farming group Klanturn in cultivating adorned plant of Chrysanthemum are knowledge, favorite, admission, environment, and leisure time while other factor such as talent, friends, and facilities do not give any influence of motivation owned by KWT Puspita’s member informing group Klantum in cultivating adorned plant of Chysanthemum.Keyword : Motivation, Chysanthemum cultivation, members of KWT Puspita.